Introduction: Exploring Post-Slavery in Contemporary Africa - Lecocq, Baz; Hahonou, Éric Komlavi (The International journal of African historical studies, 2015)
The legal abolition of slavery restructures the organizational principles in a society on the presumption that human beings should be entitled to all their legal qualities of freedom. Inspired by Stuart Hall in his reflection on postcolonialism, we could define post-slavery as a description of society in reference to a period (rather than a point) in time after the formal abolition of slavery, when power relations between masters and slaves were being reconfigured, a period that demonstrates continuities with the pre-abolition period.14 We view post-slavery as a new way to define our research agenda and its limits.